Role of the subtropical westerly jet wave train in the eastward-moving heavy rainfall event over southern China in winter: A case study - Yin, Juyue; Yuan, Junpeng; Peng, Juan; Cao, Xiaohang; Duan, Wei; Nan, Yating; Mao, Mengni; Feng, Tao (Frontiers in Earth Science, 2023)
Persistent heavy rainfall events over southern China in winter often present an eastward-propagating feature under a background of westerly winds. Heavy rainfall occurs first over southwestern China and then spreads eastward downstream to southeastern China over the following few days. We examined a six-day heavy rainfall event that occurred over southwestern China on January 8–9, 2015 and then gradually spread eastward to southeastern China on January 10–13. Our results show the important role of the Rossby wave train propagating along the subtropical westerly jet in “pushing” the eastward movement of heavy rainfall over southern China. The remote Rossby wave train influenced the variation of heavy rainfall by modifying the local circulation. The Rossby wave train can change the morphology of the East Asian subtropical jet via wave–jet interactions and modify the related secondary upward circulation in the entrance area of the jet, providing favorable dynamic conditions for the occurrence of heavy rainfall. The Rossby wave train can also influence the low-level South Branch Trough by modifying the associated baroclinic energy conversion process under a background of deep layer subsidence, which favors the transport of plentiful water vapor to the region of heavy rainfall over southern China. The eastward-propagating Rossby wave train pushed the upper level East Asian subtropical jet and the lower level South Branch Trough as a whole while simultaneously moving east, which caused the region of heavy rainfall to move from southwestern to southeastern China.